Experienced iPad-Using Early Childhood Teachers: Practices in the One-to-One iPad Classroom. Issue 1 (3rd April 2017) - Lu, Ya-Huei; Ottenbreit-Leftwich, Anne T.; Ding, Ai-Chu; Glazewski, Krista
ABSTRACT: Although many elementary schools have adopted one-to-one programs, we still lack information on how teachers integrate iPads or other tablets into their daily instruction, especially in early childhood settings. The purpose of this case study was to present how four experienced iPad-using early childhood teachers integrated one-to-one iPads into their literacy instruction. Based on observations and interviews, we found that these four teachers' used iPads in both teacher-directed and developmentally appropriate practices. The teacher-directed approaches focused on using iPads to practice basic literacy skills in different learning stations, while the developmentally appropriate approaches engaged students in child-centered digital production projects.